# Roots of a cubic equation

#### anemone

##### MHB POTW Director
Staff member
If $p,\,q,\,r$ are roots of the equation $x^3+ax^2-4x+3=0$, find the value of $\dfrac{1}{p^2}+\dfrac{1}{q^2}+\dfrac{1}{r^2}$ in terms of $a$.

Last edited:

#### Klaas van Aarsen

##### MHB Seeker
Staff member
If $p,\,q,\,r$ are roots of the equation $x^3+ax-4x+3=0$, find the value of $\dfrac{1}{p^2}+\dfrac{1}{q^2}+\dfrac{1}{r^2}$ in terms of $a$.
We have (Vieta's formulas):
\begin{aligned}
p+q+r&=-a \\
pq+pr+qr&=-4 \\
pqr&=-3 \\
\end{aligned}

Define $A=pq, B=pr, C=qr$. Then:
\begin{array}{}
A+B+C&=&-4 \\
AB+AC+BC&=&pqr(p+q+r)&=&-3 \cdot -a &=& 3a \\
A^2+B^2+C^2 &=& (A+B+C)^2 - 2(AB+AC+BC) &=& (-4)^2 - 2\cdot 3a&=&16-6a
\end{array}

Therefore:
$$\dfrac{1}{p^2}+\dfrac{1}{q^2}+\dfrac{1}{r^2} =\frac{(pq)^2 + (pr)^2 + (qr)^2}{(pqr)^2} =\frac{A^2 + B^2 + C^2}{(-3)^2} =\frac{16-6a}{9}$$

##### Well-known member
If $p,\,q,\,r$ are roots of the equation $x^3+ax-4x+3=0$, find the value of $\dfrac{1}{p^2}+\dfrac{1}{q^2}+\dfrac{1}{r^2}$ in terms of $a$.
I think you mean $x^3+ax^2-4x+3= 0$

if p, q ,r are roots of f(x) then 1/p,1/q. 1/r are roots of f(1/x) = 0

or $3x^3-4x^2+ax+1 = 0$

so $(\frac{1}{p}+\frac{1}{q} + \frac{1}{r}) = 4/3$

$(\frac{1}{pq} + \frac{1}{qr} +\frac{1}{rp} ) = a/3$

or hence $\frac{1}{p^2} + \frac{1}{q^2} + \frac{1}{r^2} = (\frac{1}{p}+\frac{1}{q} + \frac{1}{r})^2 – 2(\frac{1}{pq} + \frac{1}{qr} +\frac{1}{rp} ) = \frac{16-6a}{9}$

Last edited:

#### anemone

##### MHB POTW Director
Staff member
Hey, the two of you are doing so great today by solving my two challenge problems in such a perfect and neat way! Well done! I am looking forward to see some challenging problems to play instead...  #### soroban

##### Well-known member
Hello, anemone!

$$\text{If }p,\,q,\,r\text{ are roots of the equation}$$
$$x^3+ax-4x+3=0,\,\text{find the value}$$
$$\text{of }\tfrac{1}{p^2}+\tfrac{1}{q^2}+\tfrac{1}{r^2}\, \text{ in terms of }a.$$

From Vieta's formulas: . $$\begin{array}{ccc}p + q + r \:=\:\text{-}a &  \\ pq + qr + pr \:=\:\text{-}4 &  \\ pqr \:=\:\text{-}3 &  \end{array}$$

Square :
. . $$(pq+qr+pr)^2 \:=\: (\text{-}4)^2$$

. . $$p^2q^2 + q^2r^2 + p^2r^2 + 2p^2qr + 2pq^2r + 2pqr^2 \:=\:16$$

. . $$p^2q^2+ q^2r^2+p^2r^2 + 2\underbrace{pqr}_{\text{-}3}\underbrace{(p+q+r)}_{\text{-}a} \:=\:16$$

. . $$p^2q^2+q^2 r^2+p^2r^2 + 6a \:=\:16$$

. . $$p^2q^2+q^2r^2+p^2r^2 \:=\:16-6a$$ .

Square : .$$(pqr)^2 \:=\; (\text{-}3)^2 \quad\Rightarrow\quad p^2q^2r^2 \:=\:9$$ .

We have: .$$\frac{1}{p^2} + \frac{1}{q^2} + \frac{1}{r^2} \;=\; \frac{p^2q^2 + q^2r^2 + p^2r^2}{p^2q^2r^2}$$

Substitute  and .

Therefore: .$$\frac{1}{p^2} + \frac{1}{q^2} + \frac{1}{r^2} \;=\;\frac{16-6a}{9}$$

Last edited by a moderator:

#### anemone

##### MHB POTW Director
Staff member
Hello, anemone!

From Vieta's formulas: . $$\begin{array}{ccc}p + q + r \:=\:\text{-}a &  \\ pq + qr + pr \:=\:\text{-}4 &  \\ pqr \:=\:\text{-}3 &  \end{array}$$

Square :
. . $$(pq+qr+pr)^2 \:=\: (\text{-}4)^2$$

. . $$p^2q^2 + q^2r^2 + p^2r^2 + 2p^2qr + 2pq^2r + 2pqr^2 \:=\:16$$

. . $$p^2q^2+ q^2r^2+p^2r^2 + 2\underbrace{pqr}_{\text{-}3}\underbrace{(p+q+r)}_{\text{-}a} \:=\:16$$

. . $$p^2q^2+q^2 r^2+p^2r^2 + 6a \:=\:16$$

. . $$p^2q^2+q^2r^2+p^2r^2 \:=\:16-6a$$ .

Square : .$$(pqr)^2 \:=\; (\text{-}3)^2 \quad\Rightarrow\quad p^2q^2r^2 \:=\:9$$ .

We have: .$$\frac{1}{p^2} + \frac{1}{q^2} + \frac{1}{r^2} \;=\; \frac{p^2q^2 + q^2r^2 + p^2r^2}{p^2q^2r^2}$$

Substitute  and .

Therefore: .$$\frac{1}{p^2} + \frac{1}{q^2} + \frac{1}{r^2} \;=\;\frac{16-6a}{9}$$
Thanks for participating and well done, soroban! 